PENGUJIAN EFEK HARI DALAM SEMINGGU TERHADAP RETURNSAHAM PERUSAHAAN SEKTOR INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA - Suyanto, Dede (UI Scholars Hub, 2019)
According to the Efficient Market Hypothesis (EMH) concept, in efficient capital markets, securities prices reflect all available information. However, there is evidence of irregularities from EMH or anomalies, including the day of the week effect, the Monday Effect, Week four Effect and Rogalski Effect. Research Cross (1973) in the USA, Jaffe& Westerfield (1985) in the USA, In Indonesia, Wibowo (2004), Iramani& Mahdi (2006), Riswati (2007), Widodo (2008) showed that there was an EMH anomaly. However, these studies generally use the stock price index, therefore this study tries to use individual stock returns specifically those included in the banking industry sector after the crisis, namely 2010 - 2016. In addition, this study uses a different analytical tool, ANOVA (Analysis of Variance). According to Corhay and Rad (1994) the use of Ordinary Least Square (OLS) will be biased, because the daily stock return data tends to be abnormal, has a positive tendency with positive (leptokurtic) kurtosis. This is confirmed by the findings of Kamath, Chatrath&Chakornpipat (1998) on research in the Thai Stock Exchange. The results of this study indicate that individual stock returns show a random pattern, average returns from Monday to Friday are positive and negative and only a few are significant. Tests statistically show that the pattern of trading days is not visible or in other words, does not indicate the Monday Effect, Friday Effect, Week Four Effect, day of the Week Effect or Rogalsky Effect.